2022
DOI: 10.1111/mec.16610
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, physiological and genetic factors linked to the poleward range expansion of the snail Nerita yoldii along the shoreline of China

Abstract: Species range shift is one of the most significant consequences of climate change in the Anthropocene. A comprehensive study, including demographic, physiological and genetic factors linked to poleward range expansion, is crucial for understanding how the expanding population occupies the new habitat. In the present study, we investigated the demographic, physiological and genetic features of the intertidal gastropod Nerita yoldii, which has extended its northern limit by ~200 km over the former biogeographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…Untangling the genetic structure, population connectivity and genetic adaptation between the source and newly established population is crucial for understanding the mechanisms driving species distribution range expansion and biological invasion. Even for short‐time‐scale population distribution expansion, trends in rapid genetic adaptation can be detected (Wang et al, 2022). In the present study, our results indicate that multiple sources with divergent thermal adaptability facilitate the rapid northward distribution expansion of the southern species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Untangling the genetic structure, population connectivity and genetic adaptation between the source and newly established population is crucial for understanding the mechanisms driving species distribution range expansion and biological invasion. Even for short‐time‐scale population distribution expansion, trends in rapid genetic adaptation can be detected (Wang et al, 2022). In the present study, our results indicate that multiple sources with divergent thermal adaptability facilitate the rapid northward distribution expansion of the southern species.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics in life history help the oyster C. sikamea expand further north than other southern species. The leading edge of the geographic distribution of C. sikamea has moved northward to $34 N (Appendix S1: Figure S1), one degree north of that of its counterpart N. yoldii, the first reported intertidal species experiencing northward distribution expansion along China's coast due to land reclamation (Wang et al, 2018(Wang et al, , 2022. Life history characteristics, including reproductive mode and period, and habitat specificity, have significant influences on shaping biogeographic patterns (Hu & Dong, 2022;Pappalardo et al, 2015;Wilson et al, 2009).…”
Section: Multiple Sources Facilitate C Sikamea To Move Further North ...mentioning
confidence: 99%
“…The horizontal population differentiation or vertical differentiation of macrobenthos has been reported in previous studies (Bik et al, 2010;Ni et al, 2017;Pardo-Gandarillas et al, 2018;Sun et al, 2017Sun et al, , 2022Wang et al, 2022). However, studies of intraspecific population differentiation at both horizontal and vertical scales for epipelagic macrobenthos were still limited.…”
Section: Genetic Differentiation Pattern Of the Pelagic Barnacle Lepa...mentioning
confidence: 80%
“…In the studies of myosin heavy-chain proteins important for the muscle growth gene MYH in Pinctada fucata martensii had 18 out of 95 SNPs discovered in the exons region, were significantly associated with growth, of which 2 were confirmed in 2 populations [ 219 ]. In the studies of newly established populations of the marine snail Nerita yoldii north of the Yangtze River estuary, neutral SNPs confirmed that it consisted of founders and was distinct from the southern source population [ 220 ]. The new marginal population went through a bottleneck effect.…”
Section: Selection and Adaptation Of Aquatic Populations To Environme...mentioning
confidence: 99%